Maternal Rights Digital Activism and Intersectional Feminism: an Analysis of the Independent Media Platform “Cientista Que Virou Mãe” - Medrado, Andrea Meyer; Muller, Ana Paula (Brazilian journalism research, 2018)
This article seeks to obtain a deepened understanding of the phenomenon of maternal rights digital activism, drawing from an analysis of Cientista Que Virou Mãe (CQVM or Scientist who became a mother, in Portuguese), a blog which became an independent media platform. By doing this, we hope to fill an important research gap as little is written on the relationships between motherhood, feminism and the media. Based on preliminary evidence, we also wish to suggest that the CQVM platform can be located within the context of digital activism, arguing that the latter has lots to benefit from incorporating the perspectives of intersectional feminism. In order to achieve this, our study has a netnographic inspiration, analyzing one particular event that was significant in the history of the CQVM platform as it echoed the voices of black mothers. Neste artigo, buscamos compreender o ativismo digital materno a partir da análise de um blog que passou a operar como uma plataforma de mídia independente: o Cientista Que Virou Mãe (CQVM). Gostaríamos de apresentar os indícios que revelam que esta plataforma atua como importante iniciativa de ativismo digital materno. Tanto nos estudos feministas, como nos estudos de comunicação e mídia, este recorte, mais voltado para a análise das relações entre maternidade, feminismo e mídia, é relativamente pouco trabalhado. Após localizarmos a plataforma CQVM dentro do contexto do ativismo digital materno, destacamos que tal fenômeno pode ser beneficiado por uma maior incorporação das perspectivas do feminismo interseccional. Para demonstrar esse ponto, adotamos uma abordagem de inspiração (n)etnográfica, analisando um evento marcante na história da plataforma, o qual trouxe à tona as vozes das mulheres e mães negras. El objetivo de este artículo es conducirnos una comprensión más profunda del fenómeno del activismo digital materno, a partir de un análisis de Cientista Que Virou Mãe (CQVM, La Cientista que se Convirtió en Madre, traducido al español), un blog que se convirtió en una plataforma de medios independientes. A partir de aqui, esperamos llenar una brecha de investigación importante ya que se escribe poco sobre las relaciones entre la maternidad, el feminismo y los medios. También deseamos sugerir que la plataforma CQVM se pueda ubicar dentro del contexto del activismo digital, argumentando que este último tiene mucho que beneficiarse al incorporar las perspectivas del feminismo interseccional. Para cumplir con este propósito, nuestra investigación adopta una inspiración (n)etnográfica, analizando un evento particular que fue significativo en la historia de la plataforma CQVM ya que se manifestaron más fuertemente las voces de las madres negras.